Evaluation of Bowel Wall Thickening by Computed Tomography to Differentiate Benign from Malignant Lesions - Tapasvi, Chaitanya (J Clin Diagn Res, 2014)
Purpose: Computed tomography(CT) is an excellent non-invasive modality to evaluate bowel wall thickening.The aim of our study was to evaluate CT appearance of bowel wall thickening due to various benign and malignant conditions taking into consideration pattern of attenuation, bowel wall thickness, extent of lesion, symmetry of lesion and other associated CT findings. Materials and Methods: The prospective study was carried out on 50 patients who underwent computed tomographic evaluation of abdomen for suspicion of bowel pathology based on ultrasonography, barium studies and/or clinical grounds. The studies were conducted on Siemens ART and GE High speed CT scanners. The examination was performed as is done routinely for an abdominal scan with imaging done from diaphragm to pubic symphysis in supine position with the right lateral decubitus scans in selected cases for better characterization of gastric antral and duodenal lesions. Oral, rectal and intravenous (IV) contrast agents were administered. The diagnosis was confirmed by cytology or histopathology of any biopsy or surgical specimen. However, in cases where surgery was not done, diagnosis was confirmed by clinical response to medical treatment. Results: Based on the various CT characteristics of abnormal bowel wall thickening, sensitivity and specificity of classifying a lesion as benign or malignant were calculated. Majority of the malignant bowel lesions were showing the following characteristics i.e. heterogeneous pattern of enhancement, marked bowel wall thickening, asymmetry of the lesion and focal/segmental bowel involvement. Overall, CT showed a sensitivity of 97% and specificity of 93% in differentiating between benign and malignant etiology of abnormal bowel wall thickening. Conclusion: Due to its high sensitivity and specificity, CT is an ideal imaging modality for differentiating between benign and malignant etiology of abnormal bowel wall thickening. Radiologists should be aware of the usefulness of specific CT criteria of bowel wall thickening to better differentiate benign lesions from malignant or potentially malignant lesions that warrant further diagnostic evaluation.